(untitled) (The Research of Medical Science Review, 2025)
The increasing demand for ecologically and economically sustainable poultry production has heightened the quest for feasible alternatives to traditional protein sources, such as soybean meal and fishmeal. This study assessed the nutritional and economic effectiveness of specific alternative protein sources—Black Soldier Fly Larvae (BSFL) meal, Spirulina (Arthrospira platensis), fermented rapeseed meal, and dried brewer’s yeast—in the formulation of grill feed. Two hundred Cobb-500 grill chicks were randomly allocated to five feeding regimens in a completely randomized manner and observed over a 42-day duration at Univerisity of Agriculture, Faisalabad, Punjab, Pakistan. Growth performance, feed conversion ratio (FCR), cost efficiency, and proximate nutrient analyses were evaluated. The findings indicated that broilers consuming diets with BSFL and Spirulina demonstrated markedly greater body weight gains (2505 g and 2450 g, respectively) and reduced feed conversion ratios (1.58 and 1.66) than those on the conventional soybean-based control diet (FCR: 1.74). Moreover, these diets reduced the cost per kilogram of weight gain despite comparatively elevated ingredient expenses, indicating enhanced feed efficiency and economic viability. In contrast, rapeseed meal resulted in relatively inferior performance, possibly due to the presence of remaining anti-nutritional components. Nutritional analysis verified that all experimental meals satisfied the necessary crude protein and energy standards. These results highlight the potential of incorporating insect and algal proteins into poultry nutrition programs to improve production and sustainability. Additional research is advised to enhance inclusion levels and evaluate the long-term health implications and market viability. This study contributes to the growing body of evidence supporting the use of alternative proteins in commercial poultry systems.